Forensic Archaeology : A Global Perspective - Groen, W. J. Mike (John Wiley & Sons, Incorporated, 2015)
Title Page -- Copyright Page -- Contents -- Biographies of editors -- Biographies of contributors -- Foreword by Clyde Collins Snow -- Foreword by Jeremy Sarkin -- Foreword by Colin Hope -- Preface by W.J. Mike Groen -- Acknowledgments -- Glossary of abbreviations -- Introduction -- Part 1 Europe -- Chapter 1 Forensic archaeology and anthropology in Austria -- Introduction -- Overview of Austria -- The legal framework affecting forensic archaeology and anthropology -- Forensic archaeology and anthropology in Austria -- The demand for forensic anthropology and archaeology investigations -- The applied investigation flow for buried and surface skeletonised remains -- Training and education opportunities in forensic archaeology and anthropology -- Conclusion and future developments -- Acknowledgment -- References -- Chapter 2 DVI Belgium: victim identification and necrosearch -- Introduction -- Belgium and the Belgian police -- Conclusion -- Acknowledgements -- References -- Further Reading -- Websites -- Chapter 3 Bosnia and Herzegovina: forensic archaeology in support of national and international organisations undertaking criminal investigations and identifying the missing from 1996 to 2013 -- Historical background -- International investigations -- National investigations -- Conclusion -- Acknowledgements -- References -- Chapter 4 Forensic archaeology in Bulgaria - problems and perspectives -- Historical background -- Definition -- Medico-legal framework -- Problems -- Role and future -- Perspectives -- Conclusions -- References -- Chapter 5 Croatia (Hrvatska): from WWII and the 1991 war to contemporary forensic cases -- Introduction -- Forensic archaeology history in Croatia -- The recovery of forensically significant skeletal remains and the medico-legal framework in Croatia.